Productivity of chickpea yield capacity depending on the use of intensification elements and fertilizers under conditions of the Western Forest-Steppe - Пущак, В. І. (Scientific Progress & Innovations, 2018)
We presented the research results on the effectiveness of applying plant protection products and mineral fertilizers in the technology of chickpea growing. It was revealed that the chickpea had a low productivity (1.28 t/ha) on sowings where plant protection products were not applied due to significant growth of weeds and infections of chickpea plants. It was discovered that the chickpea’s productivity grew up to 2.30 t/ha, or by 1.02 t/ha, when the soil herbicide «Reiser» (flurochloridone, 250 g/l) was used in a concentration of 2.5 l/ha. Using of the insecticide «Fastak» (alpha-cypermethrin, 100 g/l) in a concentration of 0.15 l/ha had no effect on productivity. In case of the three-step application scheme of fungicides such as «Rex Duo» (epoxiconazole, 187 g/l + thiophanate-methyl, 310 g/l) in a concentration of 0.5 l/ha at the early phase of budding, «Abacus» (pyraclostrobin, 62.5 g/l + epoxiconazole, 62.5 g/l) in a concentration of 1.5 l/ha during flowering, and «Folikur» (tebuconazole, 250 g/l) in a concentration of 1.0 l/ha during seed filling, the productivity increased by 0.90 t/ha compared to the variant where fungicides were not applied. In total, due to the use of plant protection products in the experiment, the productivity increased from 1.28 t/ha to 3.21 t/ha, i.e. by 1.93 t/ha (150.8 %). Applying phosphorous and potassium fertilizers practically had no impact on field similarity and density of plants at the stage of seedling. When P40K60 + «Intermag legumes» + MgSO4 were used, the density of plants increased before harvesting to 7 plants per m2 compared to the variant without fertilizers. The productivity of the chickpea cultivar «Pamiat’» on the variant without applying fertilizers was 2.42 t/ha. When increasing the norms of phosphorous and potassium fertilizers, the productivity rose by 0.18–0.67 t/ha, or 7.4–27.7 %. Because of optimization of the system of use of fertilizers, the productivity increased from 2.42 t/ha on the variant without fertilizers to 3.09 t/ha on the variant where P40K60 + «Intermag legumes» + MgSO4 was used, i.e. increased by 0.67 t/ha.